OPTIMASI KONSENTRASI L-CYSTEINE PADA MODIFIKASI SINTESIS NANOPARTIKEL PERAK (AgNPs) DENGAN L-CYSTEINE - Nisaul, Cindi Fitria; Alimuddin, Alimuddin; Arif, Moh. Syaiful (JURNAL ATOMIK; Vol 8 No 1 (2023), 2023)
Modification of synthesis of nanoparticles with L-Cysteine functions as a capping agent/stabilizer, so that the nanoparticles can last longer. Modification of nanoparticle synthesis by adding L-Cysteine to AgNPs and homogenizing it using a magnetic stirrer. Modification of nanoparticles (AgNPs) was monitored by observing the visible uptake. The results showed that the absorbance value increased by indicating the concentration of L-cysteine  5×10 -5 ; 6×10 -5 ; 7×10 -5 ; 8×10 -5 ; 9×10 -5 ; 1×10 -4  and the volume of L-cysteine is 4 mL.